Using a large climate ensemble to assess the frequency and intensity of future extreme climate events in southern Africa - Thomas, Timothy S.; Schlosser, C. Adam; Strzepek, Kenneth M.; Robertson, Richard D.; Arndt, Channing (Frontiers Media, 2022)
This paper uses 7,200 smoothed climate change projections for each of the four emissions scenarios, together with inter-annual variation provided by detrended historical climate data to investigate changes in growing season (wettest 3 months) weather patterns from the 2020s to the 2060s for ten countries of Southern Africa. The analysis is done in 8,888 quarter-degree pixels by month. Temperature unequivocally rises in the region, but it rises relatively less along the coasts, particularly on the eastern side of the region. Precipitation has trended downward for much of the region since 1975, but relatively little change in precipitation is projected between the 2020s and the 2060s. Under the higher emissions “Paris Forever” scenario, we found that by the 2060s, the 1-in-20-year low-rainfall events will occur twice as frequently in most of the region, though it will occur less frequently in northwestern Angola. The 1-in-20-year high-rainfall events will occur 3 to 4 times as often in northeastern South Africa and twice as often in most of Angola.